Análisis de la sustentabilidad de los productores de tuna ( Opuntia ficus-indica) de la parroquia La Victoria cantón Pujilí, provincia de Cotopaxi. - Amores Torres, Cristian Javier (2021)
The present research work was carried out in El Tejar neighborhood, located in “La Victoria” parish from Pujilí. The aim was to analyze the sustainability of the prickly pear producers. It was used the multicriteria methodology proposed by Santiago Sarandón. Varriables and indicators were formulated to measure the sustainability of the sector. In the project’s action place, a census was applied to the entire population of prickly pear producers. Surveys with sustainability indicators were applied, where 40 qualitative and quantitative variables were analyzed for characterization. They were distributed in 12 indicators, and 41 sub-indicators immersed in the economic, environmental and sociocultural dimensions of the area. The results indicate that, the UPA of the sector present to vicia and oats as the predominant crops, and the trade as the main economic activity. In the social field, it was determined that, there is an average level of schooling, 47.05% of prickly pear producers will have secondary school studies and 29.41% of producers will have a primary education, regarding the management of the UPA, most of it is handled by women with 52.94%. The economic dimension had a value of 1.55; the social dimension was 1.88; and, the environmental dimension reached 1.06. In the sustainability evaluation, the general sustainability index was determined, it was 1.82, which shows a very low index of crop sustainability under study. After the interview, the producers indicated that, the most common pests in tuna farming are the borer and sucking insects, while the most common diseases were: Fusarium sp., Alternaria sp., And Colletrotichum sp. Finally, it is concluded that, sustainability for prickly pear producers is a new issue and the analysis shown a very low index.